Spontaneous Rupture and Hemorrhage of WON: A Case Report - Yan, Jican; Yu, Wenhao; Yan, Jingxin; Guo, Xinjian; Hou, Lizhao; Ren, Li; Fan, Haining (Frontiers in Surgery, 2022)
Background Pancreatic pseudocysts are characterized by the leakage of pancreatic juice caused by various reasons, which leads to pancreatic juice accumulates around the pancreas, and stimulates the greater omentum and other tissues to form an area of fibrotic loculated effusion with an integrated capsule. Approximately, one-third of patients experienced recurrent pancreatic juice leakage, compression symptoms, infection, and bleeding, which requires surgical intervention, but spontaneous rupture cases are extremely rare. Case presentation We here present the case of 40-year-old male who presented with abdominal pain and vomiting for two days and 10 h, respectively. He had a history of chronic pancreatitis and pseudocysts. The symptoms of abdominal pain worsened in the second day. Laboratory tests showed a progressive decrease in hemoglobin. Then, emergency pancreatoduodenectomy was performed. Intraoperative exploration found a small blood clot in the abdominal cavity and a hematoma that had formed in the intestinal cavity and retroperitoneum. Conclusion This case showed that pseudocysts of the pancreas can rupture under certain circumstances, leading to intraperitoneal bleeding and hematoma formation, which can endanger the life of the patient. And surgical treatment can be the first choice for hemorrhagic pseudocysts.